2004
DOI: 10.1038/modpathol.3800116
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration in PreservCyt®: a novel and reproducible method for possible ancillary proteomic pattern expression of breast neoplasms by SELDI-TOF

Abstract: Proteomic profiles of tumor protein expression by the surface enhanced laser desorption-ionization time of flight (SELDI-TOF) methodology have been shown to have a potential usefulness for protein discovery as well as screening, diagnosis, prognosis and therapeutic considerations of cancer from several organ systems. Fineneedle aspiration (FNA) specimens from tumor samples is an accepted method to diagnose the cells of interest but often can be a limited assessment due to quantity of the sample. The current us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The disadvantage of this method is the low amount of tissue sample for analysis. However, this problem may be overcome by using newer proteomics advances, such as SELDI-TOF, as shown in breast cancer studies [87] or by culturing in vitro biopsy cells prior to analysis, as shown in skin melanoma [88].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 98%
“…The disadvantage of this method is the low amount of tissue sample for analysis. However, this problem may be overcome by using newer proteomics advances, such as SELDI-TOF, as shown in breast cancer studies [87] or by culturing in vitro biopsy cells prior to analysis, as shown in skin melanoma [88].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 98%
“…Examples of selection surfaces include those with hydrophobic, hydrophilic, anionic or cationic properties, antibodies, nucleic acids or ligands. In breast cancer, SELDI-TOF-MS has been used to investigate serum/plasma [19][20][21], nipple aspirate fluid [22,23] and solid tumor tissues [24]. Once again, the focus to date has been on the identification of diagnostic biomarkers, but recent studies have used the technique as a potential tool to predict outcome [24,25] and to monitor cancer treatment [26].…”
Section: Proteomic Profiling Of Human Tissues and Fluidsmentioning
confidence: 99%
“…Many ancillary tests and evolving molecular techniques such as microarray and proteomics [13,22-24] require procurement of tissue specimens at various stages of management. It is critical to provide a reproducible procedure for such retrieval.…”
Section: Discussionmentioning
confidence: 99%